Becoming a Selfish Clan: Recombination Associated to Reverse-Transcription in LTR Retrotransposons - Drost, Hajk Georg (2019)
Transposable elements (TEs) are parasitic DNA bits capable of mobilization and mutagenesis, typically suppressed by host's epigenetic silencing. Since the selfish DNA concept, it is appreciated that genomes are also molded by arms-races against natural TE inhabitants. However, our understanding of evolutionary processes shaping TEs adaptive populations is scarce. Here, we review the events of recombination associated to reverse-transcription in LTR retrotransposons, a process shuffling their genetic variants during replicative mobilization. Current evidence may suggest that recombinogenic retrotransposons could beneficially exploit host suppression, where clan behavior facilitates their speciation and diversification. Novel refinements to retrotransposons life-cycle and evolution models thus emerge.